Performance Factors Contributing Enterprise Development: Finding from Survey in Kavre District - Neupane, Rabindra Kumar; Basnet, Bhupindra Jung (DEPAN, 2025)
Regarding the acknowledged importance of micro and small enterprises to both the developed and developing world, this research focuses on the factors contributing successful performance of micro-enterprises at Kavrepalancowk district promoted under the Micro-Enterprise Development (MED) model of the Ministry of Industry. Theories and researches on entrepreneurship development have indicated certain performance factors responsible for enterprise success or failures. Therefore, the general objective of this study is to analyze the effect of performance factors contributing to micro-enterprise development. Kavrepalanchok district is selected on the basis of purposive sampling due to its richness in information holdings, experience, and closer to field visit. Micro-entrepreneurs are selected based on simple random sampling. Descriptive research designed is applied in this research and the collected data is analyzed using both descriptive and inferential statistical tools. The article’s rationality is backed by its usefulness to the Government of Nepal in taking policy and program level decisions, beneficiary micro-entrepreneurs for using the benefits of this model, and other training providers to replicate the whole or useful components of this model. This research finding reveals that entrepreneurial knowledge, skills and technological access, credit facility, and access to the market have positive relationship with micro-enterprise performance significantly